Corrosion of ancient glass beads found in Southern Thailand - Won-In K. (2014)
Glass has been used as ornaments and decorations in Thailand for several hundred years. The archaeological resources suggested that the ancient glass beads excavated in southern Thailand were made more than 1300 years ago. Initial findings revealed that there were number of difference in shade between the glass beads of difference colors. Energy dispersive X-ray spectrometer (EDS) system attached with scanning electron microscope (SEM) and particle-induced X-ray emission spectroscopy (PIXE) were firstly used to study the surface corrosion of the samples. SEM micrographs showed more corroded and flaked microstructure. These were contributed to the interaction of both the ground water and its dissolved chemical compounds. © Published under licence by IOP Publishing Ltd.